Witnessing Trauma in Simon Stephens’ Motortown - Mesut Günenç (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Simon Stephens is one of the most important contemporary playwrights whose popularity spreads out both Britain and continental Europe. His Motortown (2006) consists of eight scenes. Having structural order and correlations with each other, these scenes depict notions of fear, violence, anxiety and traumatic experiences. The play’s protagonist, Danny, is a British soldier who is sent to Iraq for his military service and comes back home with his traumatic memories. Simon Stephens portrays a political play which discloses the tormenting process of Danny’s unsuccessful treatment back home. Stephens also depicts traumatic patterns and major trauma factors observed as the lack of family support and psychological disorders of contemporary British society, which are the disappointing results of war in Iraq. Applying the trauma theory and taking into consideration the effects of war, this study will illustrate Danny’s personal background and his traumatic experiences which become central among other characters in contemporary British culture.